Alkylation, alkenylation, and alkynylation of heterocyclic compounds through group 9 (Co, Rh, Ir) metal-catalyzed C-H activation. Issue 4 (2nd October 2022) - Chandra, Devesh; Dhiman, Ankit Kumar; Parmar, Diksha; Sharma, Upendra
ABSTRACT: C-H activation is a prominent tool in organic synthesis. The potential application of C-H activation in the diversification of heterocycles has attracted widespread industrial interest. Reactions involving alkylation, alkenylation, and alkynylation have an edge in modern organic synthesis and are widely employed to synthesize vital molecules. Among different metal catalysts used in C-H activation of heterocycles, group 9 (Co, Rh, Ir) metal complexes particularly MCp* have emerged as powerful catalysts. The current review is focused on the recent developments in the Group 9 transition metal (Rh, Ir, Co) catalyzed alkylation, alkenylation, and alkynylation of the heterocycles via C-H bond activation.